Randomized Controlled Trial to Evaluate the Efficacy of Oral Dexamethasone and Intramuscular Dexamethasone in Mandibular Third Molar Surgeries - Sabhlok, Samrat (J Clin Diagn Res, 2015)
INTRODUCTION: Surgical removal of impacted third molar is the most commonly performed dento-alveolar procedure and is associated with post-operative pain, swelling and trismus. AIM: The aim of the study was to compare the efficacy of dexamethasone administered orally with that of dexamethasone administered as an intra-masseteric injection in surgical removal of mandibular third molars. MATERIALS AND METHODS: Sixty patients with impacted mandibular third molars were selected to undergo surgical removal of mandibular third molars. They were divided into three groups of twenty each, viz., Control Group, Group taking Oral dexamethasone and Group taking Intra-masseteric dexamethasone. Evaluation was done over a period of seven days postoperatively to study the effects of the drug in terms of swelling, trismus and pain. RESULTS: ANOVA test was done and comparisons were made. It was found that there was a statistically significant difference with respect to the group taking oral dexamethasone in terms of resolution of trismus. It was also found that there was no statistical significance with respect to reduction in swelling in either of the groups. CONCLUSION: Thus, it can be concluded that the oral route is superior compared to the intramuscular route when administering dexamethasone in surgical removal of mandibular third molars, with respect to drug dosage, bio-availability and resolution of trismus.